Pelatihan Pembuatan Kompos Dari Campuran Limbah Daun Kering dan Basah - Asri Mulya Ashari (Indonesian Journal Publisher, 2024)
Composting is an effort to reduce waste discharge into the environment, thereby reducing environmental pollution. Compost, made from dry or wet leaves, can be used to fertilize the soil, thereby reducing the use of chemical fertilizers which over time can cause poverty in soil nutrients. Composting training for school children at SMPN 5 Kubu Raya aims to train students so they can understand the management of waste into compost and its benefits for the environment. This activity was carried out at SMPN 5 Kubu Raya school, using a lecture and demonstration method for making compost using a simple method, in the form of fermenting a mixture of dry and wet leaves in a closed container. Monitoring and evaluation of activities is carried out during the activity. The evaluation results show the ability of SMPN 5 Kubu Raya students to make compost from a mixture of dry leaves and wet leaves, and understand the importance of processing compost to be used to re-fertilize the soil.